2018
DOI: 10.1016/j.cell.2018.05.052
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Ablation Stimulates Anti-tumor Immunity and Enables Checkpoint Blockade

Abstract: Chromatin regulators play a broad role in regulating gene expression and, when gone awry, can lead to cancer. Here, we demonstrate that ablation of the histone demethylase LSD1 in cancer cells increases repetitive element expression, including endogenous retroviral elements (ERVs), and decreases expression of RNA-induced silencing complex (RISC) components. Significantly, this leads to double-stranded RNA (dsRNA) stress and activation of type 1 interferon, which stimulates anti-tumor T cell immunity and restra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
479
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(549 citation statements)
references
References 42 publications
34
479
2
Order By: Relevance
“…Expression of such ERVs promoted MHC class 1 upregulation, T‐cell infiltration, activation of immune checkpoints, and myeloid infiltration, thus promoting tumor immune suppression. On the other hand, Sheng et al demonstrated that expression of ERVs was increased following ablation of the histone demethylase LSD1 in cancer cells, which led to dsRNA stress and activation of type 1 IFNs, stimulated antitumor T‐cell immunity, and restrained tumor growth in return . Further studies are still warranted to elucidate the detailed role of HERVs in regulating immunity.…”
Section: Functional Roles Of Hervs In Carcinogenesismentioning
confidence: 99%
“…Expression of such ERVs promoted MHC class 1 upregulation, T‐cell infiltration, activation of immune checkpoints, and myeloid infiltration, thus promoting tumor immune suppression. On the other hand, Sheng et al demonstrated that expression of ERVs was increased following ablation of the histone demethylase LSD1 in cancer cells, which led to dsRNA stress and activation of type 1 IFNs, stimulated antitumor T‐cell immunity, and restrained tumor growth in return . Further studies are still warranted to elucidate the detailed role of HERVs in regulating immunity.…”
Section: Functional Roles Of Hervs In Carcinogenesismentioning
confidence: 99%
“…Specifically, it has been shown that ablation of histone demethylase LSD1 activates type I interferon, which stimulates anti-tumor T cell immunity. This elicits significant responses to checkpoint blockade in mouse melanomas which were previously refractory to anti-PD-1 therapy 165 . Similarly, the combination of interferon and anti-CTLA4 antibody had superior efficacy compared to anti-CTLA4 antibody alone in a phase Ib trial of melanoma patients 166 .…”
Section: Future Directions In Treatment With Immune Checkpoint Inhibimentioning
confidence: 99%
“…The accumulation of double-stranded RNA (dsRNA) results in the stimulation of interferon (IFN) -dependent immunogenic responses (51). These studies also show that LSD1 inhibition overcomes resistance to checkpoint blockade therapy in vivo by increasing tumor immunogenicity and T cell infiltration (51)(52)(53). Several studies have shown interaction between LSD1 and SWI/SNF complexes.…”
Section: Introductionmentioning
confidence: 98%
“…Further, recent studies indicate that LSD1 ablation can trigger anti-tumor immunity through stimulation of expression of endogenous retroviral elements (ERVs) and downregulation of expression of the RNA-induced silencing complex (RISC). The accumulation of double-stranded RNA (dsRNA) results in the stimulation of interferon (IFN) -dependent immunogenic responses (51). These studies also show that LSD1 inhibition overcomes resistance to checkpoint blockade therapy in vivo by increasing tumor immunogenicity and T cell infiltration (51)(52)(53).…”
Section: Introductionmentioning
confidence: 98%